Active Case Finding Melalui Skrining TB Paru Di Desa Kampung Delima - Ernawati Ernawati; Darmawansyah Darmawansyah; Febrina v Tamba; Nesti Untari Kadie; Wenti Rugayah; Ria Novita Rusadi (Jurnal Pengabdian Kepada Masyarakat, 2025)
Screening is not only to diagnose someone infected with a disease, it is necessary to carry out further examination by a doctor to obtain the diagnosis and treatment needed. Having Tuberculosis screening activities to actively find cases in the community will allow for an earlier reduction in Tuberculosis transmission because a person will be diagnosed earlier and has the potential to reduce the length of time a person infects other people. The aim of this community service is to detect early the risk of TB transmission in the community as an effort to prevent pulmonary tuberculosis. Implementation of service activities in the form of TB screening was carried out on July 12 2024, held in Kampung Delima Village. The target of this activity is people who live in Kampung Delima Village who are over 15 years old and are willing to take part in the activity. Service is carried out by carrying out screening activities using interview techniques using questions containing the identity of the community and followed by using a tuberculosis sign and symptoms form. The results obtained were that the majority of people in this sub-district were not at risk of contracting TB. In conclusion, participants who were not at risk of contracting TB were given education and then participants who were at risk of contracting TB were given education and advised to undergo further examination in the form of a laboratory examination at the nearest health service facility.